PENGENDALIAN KUALITAS HASIL CETAK WARNA BERDASARKAN METODA DMAIC DI PT âGâ UNIT KOMERSIAL - Renaldy, Heru; Citra, Camelia Minarry; Jessica, Jessica; Cie, Ho Hwi (Industrial and Systems Engineering Assessment Journal (INASEA), 2013)
This research analyzed printing quality at Commercial Unit of PT âGâ in Cikarang using DMAICÂ method (N=46), that implemented six sigma in its production processes. The Define level identified colorÂ stability as a significant factor for printing quality. The Measure level accessed DPMO and Sigma level forÂ color stability (ÎE) at 10,192 (Ï=3.82), and stability processes (density, dot gain, and trapping) wereÂ approximately at 413,472(Ï=1.72). Analyzes for stability processes showed some observations exceeded UCLÂ and LCL; for capability processes showed the level of color stability <1.0 (ÎE=0.82); stability processes of dotÂ gain and trapping <1.0 (density = 1.08; dot gain=0.78; trapping=0.62). Factor analysis was done utilizingÂ fishbone diagram and FMEA. At Improve level, some suggestions were recommended to increase the six sigmaÂ level. At Control level, the suggestions implemented were documented. The findings indicated that DPMOÂ decreased as much as 65.22% that implicated the increase of Ï level from 3.82 to 4.19 for color stability, fromÂ 3.33 to 3.77 for density, from 0.85 to 2.15 for dot gain, and from 1.59 to 2.49 for trapping.